A polyanion group positive electrode material precursor and preparation method thereof, positive electrode material prepared from the precursor and battery
By adopting the preparation method of the precursor of the multi-anionic group positive electrode material, the problems of poor mix uniformity and poor interface contact in the preparation of existing ternary positive electrode materials are solved, and a positive electrode material with high spherical shape, high tap density and excellent electrochemical properties are achieved .
Patent Information
- Application Number
- CN202210988265.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-08-17
AI Technical Summary
In the existing preparation methods for ternary positive electrode materials, there are problems such as poor mix uniformity and poor interface contact caused by multiphase coexistence after calcination, which affects the performance of the material.
The precursor of the polyanionic group positive electrode material is prepared by reacting the soluble salts of Mn, Ni, Co and A with salts or alkalis containing carbonate, oxalate, hydroxide, and form the precursor under the action of a complexing agent. It has high spherical shape and high tap density.
A positive electrode material with high spherical shape, high tap density and excellent electrochemical properties has achieved good results in particular in terms of rate performance and cycle stability.
Smart Images

Figure CN115385969B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery materials and electrochemistry, in particular to a polyanion group positive electrode material precursor and a preparation method thereof, a positive electrode material prepared from the precursor, and a battery. Background Art
[0002] Lithium-ion batteries were first used in 3C fields such as mobile phones and notebooks due to their high energy density, long service life and good safety. With the emergence of emerging electric vehicles and the rapid development of large-scale energy storage grids, traditional commercial lithium-ion batteries can no longer meet the demand for higher specific energy. Layered ternary cathode materials are undergoing rapid commercial penetration due to their excellent cycle performance, low price and high discharge specific capacity; lithium-rich ternary cathode materials have been widely studied in recent years due to their ultra-high specific capacity (more than 250mAh / g, even more than 300mAh / g).
[0003] The structure determines the performance, and the structure significantly affects the synthesis method. For a mature industrial product, the conditions of the entire synthesis route will determine the properties of the final product. Among the many preparation methods of ternary positive electrode materials, the method currently used in industrial production is mainly the co-precipitation method. The product obtained by the co-precipitation method is the precursor of the positive electrode material, which can be divided into hydroxide system, carbonate system and oxalate system according to the different precipitants.
[0004] Among them, if there is Mn element in the hydroxide system, it is easy to be oxidized during the drying and washing process, resulting in phase separation of the precursor. After mixing and calcining with lithium salt, locally enriched Li2MnO3 components are likely to appear, which are easy to release oxygen at high potential and cause structural damage, affecting the electrochemical properties of the material while bringing safety hazards.
[0005] The precipitates prepared by the carbonate system and / or oxalate system are more stable in the air and have strong antioxidant properties. However, when they are mixed with lithium salts and sintered, CO2 will be generated from inside the precursor, resulting in a higher porosity of the material, which reduces the density and strength of the material, restricting its practical application.
[0006] It can be seen that the above systems all have their own problems when preparing positive electrode materials. In order to improve battery performance, the prior art has modified the electrochemical properties of materials by doping. For example, patent application CN102790209A discloses a positive electrode material for a lithium ion battery, including: 1+x MX δ O ε-δCompound; wherein M is one or more of Ni, Co, and Mn; X is one or more of F, Cl, Br, I, and S; 0<x≤0.33, 0<δ≤0.2, 0<ε≤10. It provides a positive electrode material doped with anions at the oxygen position and a preparation method of a positive electrode material for a lithium ion battery. In fact, the F, Cl, Br, and I anions mentioned in the scheme are all -1 valence. When replacing the -2 valence O, the transition metal needs to change valence, and the positive electrode material formed is metastable; in addition, F, Cl and lithium ions are more tightly combined, and it is easy to form impurities LiX during calcination instead of entering the O lattice site; furthermore, Br, I, and S are large in size and difficult to enter the O lattice site. There are also materials modified by surface coating, for example, the invention patent CN 112993259 B provides a coated ternary positive electrode material, its preparation method, and lithium ion battery. The coated ternary positive electrode material comprises a ternary positive electrode active material core co-doped with aluminum, zirconium and fluorine and a coating layer coated on the surface of the core, wherein the coating layer comprises zirconium hydrogen phosphate and a boron compound. It should be noted that such doping and coating are difficult to solve problems such as poor uniformity of the mixed material and poor interface contact caused by the coexistence of multiple phases after calcination, and are not conducive to the performance of the material. Summary of the invention
[0007] The present invention focuses on the method currently widely used in the preparation of ternary positive electrode materials - coprecipitation method. In order to overcome the problems existing in the preparation of existing ternary positive electrode materials, a method for preparing a precursor of a multi-anion group positive electrode material is provided. Soluble salts of Mn, Ni, Co and A are mixed with salts or alkalis containing carbonate, oxalate and hydroxide, and react under the action of a complexing agent to form a precursor with high sphericity and high tap density. Under heating conditions, the hydroxide containing Mn in the precursor is moderately oxidized in the air, so that the single precursor particles can be compacted together. After adding lithium and calcining, the precursor containing oxalate or carbonate can generate CO2 to ensure appropriate porosity.
[0008] Furthermore, by optimizing the lithium / metal ratio and calcination conditions, a positive electrode material with high sphericity, high tap density, and excellent electrochemical properties can be synthesized, especially with good rate performance and cycle stability.
[0009] The specific plan is as follows:
[0010] A method for preparing a polyanion group positive electrode material precursor comprises the following steps:
[0011] (1) preparing a mixed salt solution: preparing soluble salts of Mn, Ni, Co and doping element A into a 0.1-4.0 mol / L aqueous solution, alcohol solution or a mixed solution of the two to obtain a solution X;
[0012] (2) Prepare a mixed alkaline solution: Add anionic group CO3 2- , C2O4 2- , OH - The salt or base is prepared into a 0.1-4.0 mol / L aqueous solution, alcohol solution or a mixed solution of the two; and ammonium ions are added as a complexing agent to obtain a solution Y;
[0013] (3) adding water or alcohol or a mixture of the two into a reaction kettle as a solvent, and simultaneously introducing the solution X obtained in step (1) and the solution Y obtained in step (2) into the reaction kettle at a flow rate ratio of 1-2:0.5-4 to react, and after the reaction is completed, washing, filtering, and drying to obtain a positive electrode material precursor;
[0014] The chemical formula of the positive electrode material precursor is: Mn x Ni y Co z A (1-x-y-z) [CO3] a [C2O4] b [OH] 2(1-a-b) , wherein x, y, z are each independently a positive number greater than 0 and less than 1, the doping element A is a metal, and 0≤(1-xyz)≤0.1; a and b are each independently a positive number greater than 0 and less than 1, and the ratio of the total molar number of Mn, Ni, Co and the doping element A to O is between 2-4.
[0015] Furthermore, in step (1), the soluble salt of Mn, Ni, Co or A is selected from at least one of their sulfates, acetates or nitrates; the doping element A is at least one of Al, Mg, Ca, Ti, V, Cr, Fe, Cu and Zn;
[0016] Optionally, in step (2), carbonate ions come from at least one of sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate; oxalate ions come from at least one of oxalic acid, sodium bioxalate, sodium oxalate, potassium oxalate or potassium bioxalate; hydroxide ions come from at least one of sodium hydroxide and potassium hydroxide; ammonium ions come from at least one of ammonia water, ammonium carbonate or ammonium bicarbonate, and preferably, the concentration of the ammonium ions is 0.01-1.0 mol / L.
[0017] Furthermore, in step (3), the reaction conditions in the reactor are as follows: the solvent in the initial reactor is water, alcohol or a mixture of the two, the volume of the solvent accounts for 20-80% of the final mixed suspension liquid, and the final mixed suspension liquid is composed of a precipitate, a soluble salt and a solvent generated by the reaction of solution X and solution Y; the temperature in the reactor is 50-75°C; the reaction time is 5-10 hours, and the reaction pH is 7.0-11; the stirring speed is 200r / min-1000r / min; after the reaction is completed, aging for 3-10 hours, followed by washing, filtering and drying;
[0018] Preferably, the solution used for washing and filtering is water, alcohol or a mixture of the two; after filtering, drying is performed at 80-120° C. for 5-15 hours.
[0019] The present invention also protects the positive electrode material precursor prepared by the preparation method of the multi-anion group positive electrode material precursor, wherein the positive electrode material precursor is spherical, has a particle size of 3-10 μm, is evenly dispersed, and has a tap density of 1.8-1.9 g / cm 3 .
[0020] The present invention also protects a positive electrode material, which is obtained by mixing the positive electrode material precursor or the positive electrode material precursor after heat treatment with a lithium source compound and then calcining at 400-900°C.
[0021] Furthermore, the heat treatment conditions of the positive electrode material precursor after the heat treatment are: temperature of 400-600° C., time of 2-10 hours;
[0022] Optionally, the calcination includes two stages, first calcination at 400-600° C. for 2-8 hours, and then calcination at 750-900° C. for 5-20 hours.
[0023] Furthermore, the ratio of the positive electrode material precursor and the lithium source compound when mixed is as follows: the total molar amount of Li element in the lithium source compound: the total molar amount of Mn, Ni, Co and doping element A in the positive electrode material precursor = 0.9 to 1.6; preferably, the lithium source compound is at least one of lithium carbonate, lithium hydroxide (hydrated), lithium oxalate, lithium chloride, lithium acetate (hydrated) or lithium nitrate;
[0024] Optionally, the tap density of the positive electrode material is 2.1-2.8 g / cm 3 In the 2.0-4.6V voltage window, the first 0.1C discharge specific capacity is 200-300mAh / g, the first coulombic efficiency is 85%-95%, and the capacity retention rate is 90-99% after 1C charge and discharge 100 times.
[0025] The present invention also protects a method for preparing a positive electrode material, comprising mixing the positive electrode material precursor, or the positive electrode material precursor after heat treatment, with a lithium source compound and calcining the mixture at 400-900°C;
[0026] Preferably, the lithium source compound is at least one of lithium carbonate, lithium hydroxide (hydrated), lithium oxalate, lithium chloride, lithium acetate (hydrated) or lithium nitrate, and the ratio of the positive electrode material precursor to the lithium source compound when mixed is as follows: the total molar number of Li ions in the lithium source compound: the total molar number of Mn, Ni, Co and doping element A in the positive electrode material precursor = 0.9 to 1.6;
[0027] Preferably, the calcination includes two stages, first calcination at 400-600°C for 2-8 hours, and then calcination at 750-900°C for 5-20 hours.
[0028] The present invention also protects an electrode comprising the positive electrode material, and a battery comprising the electrode.
[0029] Beneficial effects:
[0030] In the present invention, the preparation method of the multi-anion group positive electrode material precursor adopts an anion group CO3 2- , C2O4 2- , OH - The salt or base is configured into a 0.1-4.0 mol / L aqueous solution, alcohol solution or a mixed solution of the two. After these anionic groups are mixed, the sphericity of the precursor can be improved, thereby increasing the tap density, and at the same time solving the agglomeration problem of the precursor caused by calcination.
[0031] Furthermore, in the precursor material of the present invention, the hydroxide precursor containing Mn is moderately oxidized in the air, which can make the individual precursor particles compact together and reduce the agglomeration between the particles; after adding lithium and calcining, the precursor containing oxalate or carbonate can generate CO2, ensuring appropriate porosity to obtain a better tap density.
[0032] Furthermore, the present invention synthesizes a positive electrode material having high sphericity, high tap density and excellent electrochemical performance by optimizing the lithium / metal ratio and calcination conditions.
[0033] In summary, the preparation method of the polyanion group positive electrode material precursor provided by the present invention has a simple synthesis process and matches the current industrial process. The obtained positive electrode material has uniform element distribution, stable structure, and good rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly introduced below. Obviously, the accompanying drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0035] Figure 1 Scanning electron microscope image of the cathode material precursor synthesized in Example 1 of the present invention;
[0036] Figure 2 XRD pattern of the cathode material precursor synthesized in Example 1 of the present invention;
[0037] Figure 3 Scanning electron microscope image of the positive electrode material obtained after calcination in Example 1 of the present invention;
[0038] Figure 4 Scanning electron microscope image of the positive electrode material precursor of Comparative Example 1 of the present invention;
[0039] Figure 5 XRD diagram of the positive electrode material precursor of Comparative Example 1 of the present invention;
[0040] Figure 6 Scanning electron microscope image of the positive electrode material precursor of Comparative Example 2 of the present invention;
[0041] Figure 7 Scanning electron microscope image of the positive electrode material precursor of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0043] Example 1
[0044] This embodiment provides a positive electrode material precursor with high sphericity and high tap density and a corresponding high tap density lithium-rich positive electrode material, which are prepared according to the following steps:
[0045] (1) Preparation of mixed salt solution: Sulfate with a metal element molar ratio of 4:1:1 = Mn:Ni:Co is prepared into a 2 mol / L aqueous solution.
[0046] (2) preparing a mixed alkaline solution: preparing sodium carbonate, sodium oxalate and sodium hydroxide with an anion group molar ratio of 8:1:2 (=CO3:C2O4:OH) into a 0.5 mol / L aqueous solution; and adding ammonia water as a complexing agent, with an ammonium ion concentration of 0.05 mol / L.
[0047] (3) Deionized water is added into the reaction kettle as a solvent, and the mixed salt solution obtained in step (1) and the mixed alkali solution obtained in step (2) are simultaneously introduced into the reaction kettle at a flow rate ratio of approximately 1:4 for reaction, the pH value is controlled at 8.5, the reaction temperature is 60°C, the stirring speed is 500r / min, and the reaction is carried out for 10 hours. After the reaction is completed, the positive electrode material precursor is obtained after washing, filtering and drying.
[0048] (4) According to the molar ratio of the total metal ions of manganese, cobalt, and nickel ions to lithium ions in step (1-3) of 1:1.5, lithium carbonate and the precursor were mixed evenly, sintered at 450°C for 4h, and then sintered at 850°C for 12h to obtain the target lithium-rich positive electrode material Li 1.2 Mn 0.534 Co 0.133 Ni 0.133 O2.
[0049] (5) The positive electrode material is mixed with carbon black and PVDF in a mass ratio of 8:1:1, ground evenly with N-methylpyrrolidone as solvent, then coated on aluminum foil and placed in a blast drying oven at 100°C for 12 hours. After taking it out, roll it on a rolling machine several times and cut it into electrode discs. This is used as the positive electrode sheet, and lithium sheet is used as the negative electrode sheet. The glass microfiber filter paper GF / D produced by Whatman Company, the electrolyte is the lithium ion battery high-voltage electrolyte produced by Beijing Chemical Reagent Research Institute, and the button battery is installed in the glove box and tested on the Xinwei battery test system at room temperature 25°C.
[0050] Example 2
[0051] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: the difference between the preparation method provided in Example 1 is that in step (4), the precursor is first sintered at 500°C for 5 hours, and then the obtained oxide and lithium carbonate are evenly mixed according to the molar ratio of total metal ions of manganese, cobalt and nickel ions to lithium ions of 1:1.5, and sintered at 450°C for 4 hours, and then sintered at 850°C for 12 hours to obtain the target lithium-rich positive electrode material.
[0052] Example 3
[0053] This embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (1), metal acetate is used to replace metal sulfate, and the remaining steps are exactly the same.
[0054] Example 4
[0055] This embodiment provides a high sphericity, high tap density layered lithium-rich cathode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (1), when preparing the mixed salt solution, the sulfate with a molar ratio of metal elements of 4:1:0.025:0.025:0.025:0.025=Mn:Ni:Co:Fe:Al:Mg is configured into a 2 mol / L aqueous solution. The other conditions are exactly the same.
[0056] Example 5
[0057] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, potassium carbonate, potassium oxalate and potassium hydroxide with an anion group molar ratio of 8:1:2 (=CO3:C2O4:OH) are prepared into a 2 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction, the pH value is controlled at 8.7, and the stirring speed is 500r / min. The other conditions are exactly the same.
[0058] Example 6
[0059] The present embodiment provides a high sphericity and high tap density layered positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), lithium carbonate and the precursor are mixed evenly according to a molar ratio of total metal ions of manganese, cobalt and nickel ions to lithium ions of 1:1, and the other conditions are exactly the same.
[0060] Example 7
[0061] The present embodiment provides a high sphericity and high tap density layered positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), lithium carbonate and the precursor are mixed evenly according to the molar ratio of the total metal ions of manganese, cobalt and nickel ions to lithium ions of 1:1.4, and the other conditions are exactly the same.
[0062] Example 8
[0063] The present embodiment provides a high sphericity and high tap density layered positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), lithium carbonate and the precursor are mixed evenly according to the molar ratio of the total metal ions of manganese, cobalt and nickel ions to lithium ions of 1:1.6, and the other conditions are exactly the same.
[0064] Example 9
[0065] This embodiment provides a high sphericity, high tap density layered positive electrode material, which is prepared according to the following steps: the difference between the preparation method provided in Example 1 is that in step (4), the sintering conditions are changed to sintering at 450°C for 4 hours, followed by sintering at 800°C for 15 hours, and the other conditions are exactly the same.
[0066] Example 10
[0067] This embodiment provides a high sphericity, high tap density layered positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), the sintering conditions are changed to sintering at 450°C for 4 hours, followed by sintering at 880°C for 10 hours, and the other conditions are exactly the same.
[0068] Embodiment 11
[0069] This embodiment provides a high sphericity, high tap density, cobalt-free layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (1), when preparing the mixed salt solution, the sulfate with a metal element molar ratio of 4:2 = Mn:Ni is configured into a 2 mol / L aqueous solution. The other conditions are completely the same.
[0070] Example 12
[0071] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: the difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, sodium carbonate, sodium oxalate and sodium hydroxide with an anion group molar ratio of 9:0.5:1 (=CO3:C2O4:OH) are prepared into a 1.0 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.1 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:2 for reaction, the pH value is controlled at 8.2, and the stirring speed is 300r / min. The other conditions are exactly the same.
[0072] Embodiment 13
[0073] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, potassium carbonate, potassium oxalate and potassium hydroxide with an anion group molar ratio of 9.5:0.25:0.5 (=CO3:C2O4:OH) are prepared into a 2.0 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction, the reaction temperature is 55°C, the pH value is controlled at 9.0, and the stirring speed is 400r / min. The other conditions are exactly the same.
[0074] Embodiment 14
[0075] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, potassium carbonate, potassium oxalate and potassium hydroxide with an anion group molar ratio of 9.0:0.25:1.5 (=CO3:C2O4:OH) are prepared into a 2.0 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction, the reaction temperature is 55°C, the pH value is controlled at 9.0, and the stirring speed is 400r / min. The other conditions are exactly the same.
[0076] Embodiment 15
[0077] The present embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, potassium carbonate, potassium oxalate and potassium hydroxide with an anion group molar ratio of 9.0:0.75:0.5 (=CO3:C2O4:OH) are prepared into a 2.0 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction, the reaction temperature is 55°C, the pH value is controlled at 9.0, and the stirring speed is 400r / min. The other conditions are exactly the same.
[0078] Example 16
[0079] This embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (2), when preparing the mixed alkaline solution, ammonium carbonate is added as a complexing agent, and the ammonium ion concentration is 0.05 mol / L. The other conditions are exactly the same.
[0080] Embodiment 17
[0081] This embodiment provides a high sphericity and high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), lithium hydroxide carbon (anhydrous) is used instead of lithium carbonate. The other conditions are exactly the same.
[0082] Embodiment 18
[0083] This embodiment provides a high sphericity, high tap density layered lithium-rich positive electrode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that in step (4), lithium oxide is used instead of lithium carbonate. The other conditions are exactly the same.
[0084] Embodiment 19
[0085] This embodiment provides a high sphericity, high tap density layered lithium-rich cathode material, which is prepared according to the following steps: The difference between the preparation method provided in Example 1 is that the solvent used in the preparation of the precursor is: ethanol aqueous solution with a volume fraction of 20%, that is, ethanol aqueous solution is used to replace deionized water in step (3) and added to the reactor as the solvent. The other conditions are exactly the same.
[0086] Comparative Example 1
[0087] This comparative example provides a positive electrode material precursor and its corresponding positive electrode material. The difference between the preparation method and Example 1 is that in step (2), the alkaline solution is prepared as a 2.0 mol / L sodium carbonate aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction, and the pH value is controlled at 7.8. The other conditions are exactly the same.
[0088] Comparative Example 2
[0089] This comparative example provides a positive electrode material precursor and its corresponding positive electrode material. The difference between the preparation method and Example 1 is that in step (2), when preparing the mixed alkaline solution, sodium carbonate and sodium hydroxide with an anion group molar ratio of 9:2 (=CO3:OH) are prepared into a 2.0 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.2 mol / L. In step (3), the mixed salt solution obtained in step (1) and the mixed alkaline solution obtained in step (2) are simultaneously introduced into the reactor at a flow rate ratio of approximately 1:1 for reaction. The other conditions are exactly the same.
[0090] Comparative Example 3
[0091] This comparative example provides a positive electrode material precursor and a corresponding positive electrode material thereof, and the preparation method thereof is different from that of Example 1 in that, in step (2), when preparing the mixed alkaline solution, sodium carbonate and sodium oxalate with an anion group molar ratio of 9:1 (=CO3:C2O4) are prepared into a 0.5 mol / L aqueous solution; and ammonia water is added as a complexing agent, and the ammonium ion concentration is 0.05 mol / L. The other conditions are exactly the same.
[0092] The materials and batteries prepared in the examples and comparative examples were tested, and the results are shown in Figure 1-Figure 7 ,The test data are summarized in Table 1.
[0093] Among them, Figure 1 , 4 , 6, and 7, it can be seen that the precursor of the multi-anion group cathode material has high sphericity, uniform size, and good dispersion; Figure 4 In Comparative Example 1, the cathode material precursor is nearly spherical and relatively uniform in size; Figure 6 In the cathode material precursor of Comparative Example 2, due to the presence of OH radical groups, there are debris and the particle sphericity is poor; Figure 7 In Comparative Example 3, the cathode material precursor is said to be in agglomerated spherical shape with different sizes.
[0094] Depend on Figure 3 It can be seen that the positive electrode material obtained by mixed lithium sintering in Example 1 still maintains a spherical shape, uniform size, and good dispersion.
[0095] Figure 2 and Figure 5 is the XRD spectrum of the material, where Figure 2 This is the full XRD spectrum of the cathode material precursor of Example 1. The X-ray diffraction pattern of the cathode material precursor presents three sets of diffraction peaks, corresponding to the X-ray diffraction patterns of carbonate, oxalate and hydroxide. In particular, when the anode target is a copper target, characteristic diffraction peaks of hydroxide and oxalate appear between 2θ angles of 15-20°.
[0096] Figure 5This is the full XRD spectrum of the cathode material precursor of Comparative Example 1, in which the carbonate phase is the main phase, but at the position of 2θ=18°~20°, there is no diffraction peak corresponding to the oxalate and hydroxide precursors.
[0097] Table 1 Performance data of positive electrode material precursor and positive electrode material corresponding to the examples and comparative examples
[0098]
[0099]
[0100] Table 1 presents the properties and performance data of the positive electrode material precursor and positive electrode material corresponding to the embodiments and comparative examples, which have the following characteristics:
[0101] (1) By comparing Examples 1-19 and Comparative Examples 1-3, it can be seen that the polyanion group positive electrode material precursor exhibits a higher tap density as a whole, and the corresponding positive electrode materials (except for the non-lithium-rich Example 6) show higher tap density, first coulomb efficiency, first discharge specific capacity, 1C discharge specific capacity, and 1C100 cycle capacity retention rate.
[0102] (2) By comparing Examples 1 and 2, it can be seen that calcining the precursor first helps to increase the tap density of the positive electrode material after sintering, but the performance is slightly reduced.
[0103] (3) By comparing Examples 1, 6, 7, and 8, it can be seen that the ratio of metal and Li content significantly affects the tap density and electrochemical performance of the material, and an appropriate ratio can be considered according to specific needs. For example, when the total number of moles of Li ions in the lithium source compound: the total number of moles of Mn, Ni, and Co in the positive electrode material precursor = 0.9 to 1.6, the resulting positive electrode material has a higher tap density and exhibits better rate performance and cycle stability during the charge and discharge process.
[0104] (4) By comparing Examples 1, 9, and 10, it can be seen that the calcination conditions can also significantly affect the tap density and electrochemical properties of the positive electrode material. Appropriate temperature and calcination time can bring out the optimal performance of the positive electrode material in a specific ratio. When the molar ratio of the sum of metal Mn, Ni, and Co to Li is 1:1.5, the preferred calcination conditions are calcination at 450°C for 4 hours and sintering at 850°C for 12 hours.
[0105] (5) By comparing Examples 1, 17, and 18, it can be seen that different lithium sources can also affect the tap density and electrochemical properties of the positive electrode material. Appropriate lithium salts and mixed lithium salts can be selected according to specific needs. For example, when the lithium source compound in step (4) is lithium oxide, the tap density of the positive electrode material can be increased, but the electrochemical performance is slightly reduced; when the lithium source compound is lithium carbonate, the rate performance and cycle stability of the battery can be improved.
[0106] (6) By comparing Examples 1 and 19, it can be seen that the choice of solvent can also affect the properties of the precursor and the corresponding positive electrode material. The optimization of the solvent can further improve the electrochemical performance of the material. Considering the cost, synthesis safety and material performance, deionized water is preferably used as the solvent in step (3), which can improve the low-rate performance and high-rate cycle stability of the battery.
[0107] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0108] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0109] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a polyanion group positive electrode material precursor, characterized in that: The following steps are involved: (1) preparing a mixed salt solution: preparing soluble salts of Mn, Ni, Co and doping element A into a 0.1-4.0 mol / L aqueous solution, alcohol solution or a mixed solution of the two to obtain a solution X; (2) Prepare a mixed alkaline solution: Add anionic group CO3 2- , C2O4 2- , OH - The salt or base is prepared into a 0.1-4.0 mol / L aqueous solution, alcohol solution or a mixed solution of the two; and ammonium ions are added as a complexing agent to obtain a solution Y; (3) adding water or alcohol or a mixture of the two into a reaction kettle as a solvent, and simultaneously introducing the solution X obtained in step (1) and the solution Y obtained in step (2) into the reaction kettle at a flow rate ratio of 1-2:0.5-4 to react, and after the reaction is completed, washing, filtering, and drying to obtain a positive electrode material precursor; The chemical formula of the positive electrode material precursor is: Mn x Ni y Co z A (1-x-y-z) [CO3] a [C2O4] b [OH] 2(1-a-b) , wherein x, y, z are each independently a positive number greater than 0 and less than 1, the doping element A is a metal, and 0≤(1-xyz)≤0.1; a and b are each independently a positive number greater than 0 and less than 1, and the ratio of the total molar number of Mn, Ni, Co and the doping element A to O is between 2-4.
2. The method for preparing a polyanion group positive electrode material precursor according to claim 1, characterized in that: In step (1), the soluble salt of Mn, Ni, Co or A is selected from at least one of their sulfates, acetates or nitrates; and the doping element A is at least one of Al, Mg, Ca, Ti, V, Cr, Fe, Cu and Zn.
3. The method for preparing a polyanion group positive electrode material precursor according to claim 2, characterized in that: In step (2), the carbonate ions are from at least one of sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate; the oxalate ions are from at least one of oxalic acid, sodium bioxalate, sodium oxalate, potassium oxalate or potassium bioxalate; the hydroxide ions are from at least one of sodium hydroxide and potassium hydroxide; and the ammonium ions are from at least one of ammonia water, ammonium carbonate or ammonium bicarbonate.
4. The method for preparing a polyanion group positive electrode material precursor according to claim 3, characterized in that: The concentration of the ammonium ion is 0.01-1.0 mol / L.
5. The method for preparing a polyanion group positive electrode material precursor according to any one of claims 1 to 4, characterized in that: In step (3), the reaction conditions in the reactor are as follows: the solvent in the initial reactor is water, alcohol or a mixture of the two, the volume of the solvent accounts for 20-80% of the final mixed suspension liquid, and the final mixed suspension liquid is composed of a precipitate, a soluble salt and a solvent generated by the reaction of solution X and solution Y; the temperature in the reactor is 50-75° C.; the reaction time is 5-10 hours, and the reaction pH is 7.0-11; the stirring speed is 200 r / min-1000 r / min; after the reaction is completed, aging is performed for 3-10 hours, followed by washing, filtering and drying.
6. The method for preparing a polyanion group positive electrode material precursor according to claim 5, characterized in that: The solution used for washing and filtering is water, alcohol or a mixture of the two; after filtering, drying is performed at 80-120° C. for 5-15 hours.
7. The positive electrode material precursor prepared by the method for preparing a multi-anion group positive electrode material precursor according to any one of claims 1 to 6, characterized in that: The X-ray diffraction pattern of the cathode material precursor presents three sets of diffraction peaks, corresponding to the X-ray diffraction patterns of carbonate, oxalate and hydroxide; the cathode material precursor is spherical, with a particle size of 3-10 μm, and is evenly dispersed, with a tap density of 1.8-1.9 g / cm 3 .
8. The cathode material precursor according to claim 7, characterized in that: When the anode target is a copper target, characteristic diffraction peaks of hydroxide and oxalate appear at 2θ angles between 15° and 20°.
9. A positive electrode material, characterized in that: The positive electrode material precursor according to claim 7 or 8 or the positive electrode material precursor after heat treatment is mixed with a lithium source compound and then calcined at 400-900°C to obtain it.
10. The positive electrode material according to claim 9, characterized in that: The heat treatment conditions of the positive electrode material precursor after the heat treatment are: temperature of 400-600° C. and time of 2-10 hours.
11. The positive electrode material according to claim 10, characterized in that: The calcination includes two stages, first calcination at 400-600° C. for 2-8 hours, and then calcination at 750-900° C. for 5-20 hours.
12. The positive electrode material according to any one of claims 9 to 11, characterized in that: The positive electrode material precursor and the lithium source compound are mixed in a ratio of the total molar amount of Li element in the lithium source compound: the total molar amount of Mn, Ni, Co and doping element A in the positive electrode material precursor = 0.9 to 1.
6.
13. The positive electrode material according to claim 12, characterized in that: The lithium source compound is at least one of lithium carbonate, lithium hydroxide hydrate, lithium oxalate, lithium chloride, lithium acetate hydrate or lithium nitrate.
14. The positive electrode material according to claim 12, characterized in that: The tap density of the positive electrode material is 2.1-2.8 g / cm 3 In the 2.0-4.6V voltage window, the first 0.1C discharge specific capacity is 200-300mAh / g, the first coulombic efficiency is 85%-95%, and the capacity retention rate is 90-99% after 1C charge and discharge 100 times.
15. A method for preparing a positive electrode material, characterized in that: The positive electrode material precursor according to claim 7 or 8, or the positive electrode material precursor after heat treatment, is mixed with a lithium source compound and then calcined at 400-900°C.
16. The method for preparing the positive electrode material according to claim 15, characterized in that: The lithium source compound is at least one of lithium carbonate, lithium hydroxide hydrate, lithium oxalate, lithium chloride, lithium acetate hydrate or lithium nitrate. The ratio of the positive electrode material precursor and the lithium source compound when mixed is as follows: the total molar number of Li ions in the lithium source compound: the total molar number of Mn, Ni, Co and doping element A in the positive electrode material precursor = 0.9 to 1.
6.
17. The method for preparing the positive electrode material according to claim 15, characterized in that: The calcination includes two stages, first calcination at 400-600° C. for 2-8 hours, and then calcination at 750-900° C. for 5-20 hours.
18. An electrode comprising the positive electrode material according to any one of claims 9 to 14.
19. A battery comprising the electrode according to claim 18.
Citation Information
Patent Citations
Coated ternary cathode materials, their preparation methods and lithium-ion batteries
CN112993259B
Preparation method of layered lithium-rich manganese base oxide of positive material of lithium ion battery
CN102683645A
Positive pole material of lithium ion battery and preparation method thereof
CN102790209A